Assessment and timing of the anthropogenic imprint and fisheries richness in marine sediments from Ría de Muros (NW Iberian Peninsula). (20th November 2020) - Álvarez-Iglesias, P.; Andrade, A.; Rey, D.; Quintana, B.; Bernabeu, A.M.; López-Pérez, A.E.; Rubio, B.
Abstract: Textural, geochemical and geochronological analyses on two gravity and two box cores recovered from the outer and inner sectors of the Ría de Muros allowed reconstructing and timing the anthropogenic imprint on the sedimentary record from this ría. The chronological framework for the last 8 kyr was built based on Pb-210 dating (Constant Rate of Supply model) and C-14 dating. Recent sedimentation rates were an order of magnitude higher than those of the oldest analyzed sediments, and the periods of upwelling enhancement were constrained. Assessing the human influence on sediment metal contents required the establishment of local background levels. Since the 16th century the enrichment factors of copper, zinc and lead increased (up to 2.7, 1.5 and 2.1, respectively, at or close to present), and a remarkable increase in the fine-grained particles' content happened in the outer ría sector, due to deforestation. The anthropogenic signature identified in the sedimentary record is assigned to fishing, harbor activities, mining, salting, and, or canning activities, depending on the considered period, which caused a local demographic increase since the 16th century in the region. Such population growth caused a rise in the marine signature of the organic matter, which likely results from enhanced primary production due to eutrophication caused by increased soil erosion and human and livestock waste inputs. Furthermore, the metal enrichment trend during the 20th century, which was more significant in the inner than in the outer ría sector, follows the different demographic evolution of the villages (related to urban and industrial development). The present study highlights the need for conjunction of varying dating techniques when reconstructing the anthropization trends in coastal environments.